Contributions of Ergonomics, Psychological Factors, and Sleep Disturbances to Lower Back Pain Among Taiwanese Workers. Issue 9 (September 2021) - Shih, Ping; Chu, Po-Ching; Liu, Li-Wen; Chen, Chih-Yong; Guo, Yue Leon
Abstract : Objective: We investigated the contributions of ergonomics, psychological factors, and sleep disturbances to lower back pain (LBP). Methods: A nationwide survey of sampled 27, 508 (2.6‰) Taiwanese workers was conducted in 2010. Definition of outcome was LBP affecting work performance in the past year. Predictor variables included age, body mass index, ergonomic factors, job control, psychological demands, and sleep disturbances. Mutually adjusted relative risks were examined using general linear models, followed by aPAR. Results: 18, 353 workers were included in the multivariate regression model. The three first significant risk factors to LBP included heavy lifting or awkward posture, sleep disturbances, and high psychological demands (aPAR = 13.5%, 8.7%, 5.7% respectively in men and 6.1%, 11.8%, 5.9% in women). Conclusions: In addition to ergonomic exposure, sleep disturbances and high psychological demands significantly contributed to LBP.